2007
DOI: 10.1074/jbc.m607439200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Non-canonical Activity of Uracil DNA Glycosylase for Class Switch Recombination

Abstract: Activation-induced cytidine deaminase (AID) and uracil DNA glycosylase (UNG) are required for class switch recombination (CSR). AID is involved in the DNA cleavage step of CSR, but the precise role of UNG is not yet understood. Mutations and deletions are footprints of abortive DNA cleavage in the immunoglobulin switch region in splenic B cells stimulated to undergo CSR. However, a UNG deficiency did not reduce the number of such footprints, indicating UNG is dispensable for the DNA cleavage step. Mutagenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 70 publications
(62 reference statements)
5
52
1
Order By: Relevance
“…The N terminus of UNG is unique in that it possesses proliferating cell nuclear antigen (PCNA) and replication protein A (RPA) interacting sites (see Fig. S3), but the the region is not necessary for CSR (26,28). However, Guenzel et al (22) found that UNG-RPA interaction is necessary to suppress the mutation frequency in HIV-1, which is in contrast to what we observed in the case of AID-induced s-SHM.…”
contrasting
confidence: 63%
See 2 more Smart Citations
“…The N terminus of UNG is unique in that it possesses proliferating cell nuclear antigen (PCNA) and replication protein A (RPA) interacting sites (see Fig. S3), but the the region is not necessary for CSR (26,28). However, Guenzel et al (22) found that UNG-RPA interaction is necessary to suppress the mutation frequency in HIV-1, which is in contrast to what we observed in the case of AID-induced s-SHM.…”
contrasting
confidence: 63%
“…Curiously, this recruitment is independent of its catalytic activity but dependent on the WxxF motif of UNG, which mediates interaction with the HIV-1 accessory protein Vpr. Interestingly, the WxxF motif was also found to be a critical site for CSR (26). Requirement of a noncanonical activity of UNG was proposed in AID-induced CSR (27,28), especially because no correlation could be found between CSR efficiency and catalytic activity of UNG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA glycosylases are subdivided into four groups according to their substrate specificity: excision of uracil, uracil-containing mismatches, alkylated bases and oxidized bases (Begum et al 2007). NtROS proteins are structurally related to Arabidopsis ROS1 and DME, which belong to a large family of uracil-containing mismatch DNA glycosylases.…”
Section: Discussionmentioning
confidence: 99%
“…Their induction profile upon abiotic stresses is indicative, as DNA glycosylases are considered to deal with oxidative damages, which are commonly caused by reactive oxygen species (Choi and Sano 2007;Begum et al 2007). The NtROS2a gene was induced expression after ABA, cold, salt and H 2 O 2 treatments.…”
Section: Discussionmentioning
confidence: 99%